Scanning electron microscope analysis of Emiliania huxleyi samples revealed the presence of a single morphotype in the Dardanelles Strait, Turkey (Ocean and Coastal Research, 2022)
The cosmopolitan coccolithophorid, Emiliania huxleyi form populations composed of diferent morphotypes distinguished based on coccolith ultrastructure. The relative abundance of these morphotypes varies along the gradients of several environmental factors, including temperature, pH and nutrients, with significant ecological and biogeochemical outcomes as morhotypes difer in the calcite content, hence in their contributions to the downward carbonate transport. A scanning electron microscope examination of Emiliania huxleyi cells and coccoliths was conducted on samples from an Emiliania huxleyi dominated coastal phytoplankton community formation captured on the 29th and 31th of May 2019, performing a morphological and morphometric analysis and an assessment of the environmental nutrient characteristics. The main aim of the study was to describe the morphotype from a highly important ecosystem with E. huxleyi blooms, the Dardanelles Strait, Turkey and contribute to the present scientific understanding of their ecological preferences. The satellite-derived chlorophyll a and particulate inorganic carbon concentrations data were also included to expand the spatio-temporal coverage of the study. The nutrient data suggested nitrogen limitation of the phytoplankton community in general and an additional silicate limitation of the diatoms. The microscopic observations of samples, coccosphere/coccolith counts and the morphologic and morphometric examination of the coccoliths showed the presence of an E. huxleyi bloom solely composed of morphotype A. Furthermore, the satellite data showed the coccolithopore bloom started in the interconnected basin of the Black Sea and progressed into the Dardanelles via the Sea of Marmara.